Analytic models of domain-averaged Fermi holes: a new tool for the study of the nature of chemical bonds - Ponec, Robert; Cooper, David L; Savin, Andreas (Chemistry (Weinheim an der Bergstrasse, Germany), 2008)
Simple analytical models are introduced that significantly enhance the ability to understand and rationalise the nature of bonding interactions depicted by domain-averaged Fermi hole (DAFH) analysis. The examples presented show that besides shedding new light on the role of electron-sharing in ordinary two-centre two-electron (2c-2e) chemical bonds that are well represented by the classical Lewis model, the proposed approach also provides interesting new insights into the nature of bonding interactions that go beyond the traditional Lewis paradigm. This is, for example, the case of 3c-2e multicentre bonding, but a straightforward extension of the approach also reveals for direct metal-metal bonding the existence of a completely new type of bonding interaction that involves the mutual exchange of electrons between the lone pairs on adjacent metal atoms.